(untitled) (SCIÉNDO INGENIUM, 2022)
The present research paper, has as purpose, for which the following question has been raised: How does Corporate Social Responsibility influence the Corporate Image of Caja Trujillo in the Province of Trujillo, Period 2016-2017?. and the hypothesis is Corporate Social Respon-sibility significantly influences the Corporate Ima-gen of Caja Trujillo in the Province of Tru-jillo, Period 2016-2017. The study population was 290 people included among clients, col-laborators and the community of the Municipal Savings and Credit Fund of Trujillo. The cor-relational design was also used. The method used is deductive, hypotheses and synthesis analysis and the techniques used were the survey. The most important findings were: that there is a positive influence between Corporate Social Responsibility and the corporate image of Caja Municipal de Ahorro y Crédito de Trujillo S.A., influencing through the last four rel-evant factors such as internal social, economic, ecological and social cultural and foreign pol-icy. It is recommended: The corporate image is the result that the institution offers to others, as described in it, the clients judge it. In this sense, the Trujillo box should strengthen corporate responsibility, even more, in the field of economy and ecology.